Self-construction as a specialist for young teachers - I. T. Gasieva (Вестник университета)
The article is devoted to the study of self-construction as a professional and a reference (ideal image) professional among young teachers of secondary schools of the Republic of North Ossetia – Alania. The article empirically studies the content component of the image of the Self as a professional and the image of the Self as an ideal teacher. In the course of the research, it was revealed that the majority of young teachers surveyed identify themselves with the reference image of a professional in their chosen professional activity. The structure of the self-construction and the reference self- construction is dominated by the social component; young professionals whose self-construction does not coincide with the reference image position themselves as disillusioned with their chosen professional activity.